Hubungan Perilaku PSN terhadap Insiden DBD di Wilayah Jawa Barat : Data SKI 2023 - Alifia Nadhimah Putri; Ahmad Daffa’ Aushof; Suci Ratu Masyeni (KOLONI, 2026)
Dengue Hemorrhagic Fever (DHF) remains an endemic disease with a significant impact on public health in West Java, particularly in densely populated areas. Mosquito breeding prevention (PSN) behaviors such as 3M Plus are essential to interrupt dengue virus transmission caused by Aedes aegypti, yet their implementation is often inconsistent and not comprehensive. This condition allows vectors to breed and increases the risk of transmission. Therefore, this study aims to determine the relationship between PSN behavior and the incidence of Dengue Hemorrhagic Fever (DHF) in West Java. This study used data from the 2023 Indonesian Health Survey with a cross-sectional design. A total of 49,271 individuals in West Java were included. The dependent variable was DHF incidence, while independent variables included larvicide use, mosquito screen installation, draining water containers, covering water containers, and eliminating discarded items. Data were analyzed using univariate and bivariate methods with logistic regression at p<0.05. The results showed that larvicide use (OR=1.40; 95% CI=1.01–1.93; p=0.040), mosquito screens (OR=1.59; 95% CI=1.24–2.02; p=0.000), covering water containers (OR=1.51; 95% CI=1.19–1.90; p=0.001), and eliminating discarded items (OR=1.53; 95% CI=1.21–1.93; p=0.000) were significantly associated with DHF incidence. Meanwhile, draining water containers was not significantly associated (OR=1.21; 95% CI=0.92–1.58; p=0.158). In conclusion, several PSN